Cloning of the murine homolog of the ocular albinism type 1 (OA1) gene: sequence, genomic structure, and expression analysis in pigment cells. - Bassi, M T; Incerti, B; Easty, D J; Sviderskaya, E V; Ballabio, A (Genome Research, 1996)
We report the isolation of the mouse homolog of OA1, the gene responsible for ocular albinism type 1. The mouse Oa1 gene encodes a putative protein of 405 amino acids displaying a high level of homology (78% identity, 87% similarity) to the human gene. All disease-associated missense mutations reported in patients with ocular albinism involve conserved amino acid residues in the mouse protein. Moreover, the murine homolog shows six putative transmembrane domains, as observed for the human gene, indicating that the overall structure of the two proteins is conserved. The genomic organization is also conserved between the two species across the entire coding region with splice sites located in the same positions. Like its human counterpart, the expression pattern of Oa1, apart from the eye, is restricted to the epidermal melanocyte lineage. A transcript of approximately 1.8 kb was readily detected by this probe in 5 out of 5 murine melanocyte lines, 4 out of 4 murine melanoblast lines, 1 out of 2 murine melanoma lines, and 1 out of 2 human melanoma lines tested, but it was not detected in 2 out of 2 lines of a developmentally earlier normal cell type, melanoblast precursor cells, suggesting that the gene is transcriptionally activated in epidermal melanocytes at the same stage as most other tested melanosomal proteins. Together, these data suggest that the function of the OA1 gene is conserved between human and mouse and point to the mouse as a model to facilitate the understanding of ocular albinism pathogenesis.